Introduction of a Divergent Canine Parvovirus Type 2b Strain with a Dog in Sicily, Southern Italy, Through the Mediterranean Sea Route to Europe - Francesco Mira; Giovanni Franzo; Giorgia Schirò; Domenico Vicari; Giuseppa Purpari; Vincenza Cannella; Elisabetta Giudice; Martino Trapani; Anna Carrozzo; Giada Spene; Virginia Talarico; Annalisa Guercio (Pathogens)
Despite over four decades since its emergence, canine parvovirus type 2 (CPV-2) remains a relevant disease for dogs. Few studies, primarily only recent ones based on phylodynamic and phylogeography approaches, have highlighted the impact of rapid and long-distance transport of dogs on the CPV-2 spreading dynamics. The present study reports the genomic characterization of a CPV-2 strain detected in a dog introduced into Italy from the coasts of North Africa through the Mediterranean Sea route to Europe. The nearly complete CPV-2 sequence was obtained and analyzed. The viral isolate was characterized as a CPV-2b variant, showing genetic signatures distinct from those of CPV-2 strains detected to date in Europe. Phylodynamic and phylogeographic approaches revealed a close correlation with CPV-2 strains recently reported in the Middle East (Turkey and Egypt), which likely originated or co-evolved from Asian ones. It is at least suggestive that the inferred spreading pattern overlaps with the routes often followed by migrants travelling from Asia and Middle East to Europe, passing through Africa. This evidence for the introduction of CPV-2 via the Mediterranean Sea route to Europe highlights the relevant role of the dog movements in the global spread of emerging or re-emerging viral pathogens.